(untitled) - Bernard Hartley (New York, 1996)
This book is designed to follow "Departures" and "Connections", consolodating and building upon the oral skills. The material consists of 80 units, each clearly laid out on a separate page
Keywords: americanism,english language - textbooks for foreign speakers,english language - united states